PENGARUH PENGGUNAAN SCREEN TIME TERHADAP SPEECH DELAY PADA BALITA: KAJIAN LITERATUR - Adelia Anggretha Malau; Sipriana Anggi M. Br Simanjorang; Veronika Sitanggang; Evanny Indah Manurung; Ester Silitonga (Jurnal Perawat Indonesia, 2023)
Screen time is the exposure time to digital media such as television, video games, and other technologies that use digital screens. During the COVID-19 pandemic, screen time in toddlers has increased so much that it affects the process of toddler development. One of the social development disorders due to screen time is speech delay. Speech delay is a delay in speech ability that is not appropriate for the age of a toddler. This study aims to identify the effect of screen time on speech delay in toddlers based on a literature review. The method used is thematic analysis: a simplified approach by searching articles using the EBSCO, CORE, PubMed, and PMC databases. Articles were selected using the PRISMA flow chart and the JBI Critical Appraisal Checklist for Analytical Cross-Sectional Studies to analyse the quality of the articles. Researchers use the boolean operators "AND" and "OR" with the keywords effect, speech delay, screen time, and toddler. The results of the literature review found three themes that explain the effect of using screen time on speech delay in toddlers, namely the duration of using screen time in toddlers, the negative impact of screen time on toddlers, and the risk of speech delay from using screen time in toddlers. The conclusion of this literature review is that screen time influences speech delays in toddlers. The use of screen time that is greater than the AAP (American Academy of Pediatrics) recommendation has a higher risk of experiencing speech delay.